Rondas y canciones y su impacto en el desarrollo del lenguaje en los niños de 4 años de educación inicial Unidad Educativa “Amarilis Sandoya Cepeda” - Briones Ronquillo, María Mariuxi (2023)
The present study focused on analyzing the influence of rounds and songs on the language development of 4-year-old children at the "Amarilis Sandoya Cepeda" Educational Unit in the city of Baba. It was noted that this group presents difficulties in their linguistic growth. In this context, the theoretical bases that support the use of rounds and songs as effective strategies for language development were investigated. The type of research is qualitative, with a non-experimental design of an exploratory nature, where the deductive, analytical and synthetic method was used to analyze the collected data. The findings revealed that the majority of respondents recognize rounds and songs as effective teaching strategies and consider that they provide benefits for language development, socialization, creativity and motivation in children. Appropriate stimulation through interaction and play, in an environment rich in stimuli, favors the comprehensive development of language in this group of children, contributing to improving the quality of early education and enhancing their language skills for effective communication. Based on the results, the application of innovative strategies based on rounds and songs is recommended to address difficulties in language development since they complement and enrich existing educational practices. In addition, the need for further research in this field is emphasized in order to obtain a more complete understanding of the benefits of rhymes and songs in the development of children's language.